Modifikasi Elektrode Glassy Carbon Dengan Nanopartikel Emas Dan Aplikasinya Untuk Mendeteksi Kromium(VI) Secara Voltammetri Pulsa Differensial - Santhy Wyantuti; Mahendra Permadi; Diana Hendrati; Yeni Wahyuni Hartati (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
Chromium(VI) is very toxic and has been classified as a carcinogen in humans breathing. Purpose of this experiment is to analyze chromium(VI ) in voltammetry using a glassy carbon electrode modified with gold nanoparticles. Voltammetry method is a method of measuring the current generated from a given potential to the working electrode so that the electrode can be widely modified work. The procedures were produce pencil graphite electrode that was coated by gold nanoparticles and measured chromium(VI) signal. From this study obtained a detection limit of 12.70 ppm and 99.99% precision measurement and measurement of 0.8 V deposition potential, deposition time of 120 seconds and a scan rate of 0.01 V/s optimum.